HUBUNGAN PENDIDIKAN IBU DAN PANJANG BADAN LAHIR TERHADAP KEJADIAN STUNTING PADA BALITA USIA 12-60 BULAN DI DESA MALLUSETASI KEC. SIBULUE - Mutmainnah Mutmainnah; St. Malka St. Malka; Musni Musni (Universitas Pahlawan Tuanku Tambusai, 2022)
Mid-term health development for the 2015-2019 period, the prevalence of toddlers (stunting) is one of the priorities in four programs, namely reducing maternal and infant mortality, reducing the prevalence of toddlers (stunting), controlling infectious and non-communicable diseases. Stunting is one of the chronic malnutrition problems caused by long-term nutritional deficiencies characterized by stunted children of their age. The impact of stunting apart from health factors will also affect socio-economic life. The research method uses an analytical survey with a cross-sectional design. The sample in this study amounted to 84 mothers, the sampling technique was purpossive sampling. From the results of the study, a statistical test analysis using the Chi-Square test showed that there was no effect of maternal education level on the incidence of stunting with p value = 0,0827 (p>0,05). While the length of the birth match and the incidence of stunting in toddlers aged 12-60 months. Keywords: Stunting, length of birth, level of education